INFLUENCE OF MEVALONIC ACID AND LINALOOL ON LIMONENE ACCUMULATION IN CALLUS TISSUES OF CITRUS GRANDIS OSBECK - ZARINA ZAKARIA; NIK NORULAINI NIK AB RAHMAN; MOHD OMAR ADD KADIRS (BIOTROPIA, 2003)
Effect on callus growth was studied for Citrus grandis  cultured with feeding of exogenous mevalonic acid (MVA) at concentrations of 0.04, 0.08, 0.38, 0.77, 1.15 and 1.54 mM. Similar effect with linalool ranging from 10 to 200 nl was studied under various incubation periods. The growth was proportional to the concentrations of precursors used meaning that higher precursors concentrations influenced more growth on C. grandis callus culture. Mevalonic acid and linalool showed quite similar precursor feeding effects on limonene accumulation of C. grandis callus cultures. It was revealed that limonene production was triggered with the introduction of MVA and linalool even at low concentration. Limonene accumulation was detected as early as week four and continued to increase at about 0.0030 and 0.0032 mg/g with MVA and linalool, respectively, after the seventh week incubation. In comparison to the unfed cultures, no limonene was detected from the callus up to eight weeks in incubation. Keywords :   C/rrusgrarafo/Limonene/Linalool/Mevalonic acid Abbreviations: 2,4-D: 2,4 — Dichlorophenoxyacetic acid, ABA: Abscisic acid, MVA : Mevalonic acid